2011
DOI: 10.1017/s0007123411000317
|View full text |Cite
|
Sign up to set email alerts
|

Authoritarian Institutions and Regime Survival: Transitions to Democracy and Subsequent Autocracy

Abstract: This article examines how authoritarian parties and legislatures affect regime survival. While authoritarian legislatures increase the stability of dictators, political parties – even when devised to quell internal threats – can destabilize dictators. The main argument is that authoritarian parties influence the distribution of power in a subsequent new democracy by helping to protect the interests of authoritarian elites. These institutions thus increase the likelihood of democratization. Using a dataset of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(104 citation statements)
references
References 48 publications
(2 reference statements)
3
98
2
1
Order By: Relevance
“…Results are robust after controlling for the presence of military regimes (model E), which is the highest form of military access to decision making. A discerning feature of military regimes is the armed forces' effort to protect their corporate interests (Wright & Folch, 2012) and their continuing concern about professional unity (Geddes, 2003). These features are found to boost military spending.…”
Section: Resultsmentioning
confidence: 99%
“…Results are robust after controlling for the presence of military regimes (model E), which is the highest form of military access to decision making. A discerning feature of military regimes is the armed forces' effort to protect their corporate interests (Wright & Folch, 2012) and their continuing concern about professional unity (Geddes, 2003). These features are found to boost military spending.…”
Section: Resultsmentioning
confidence: 99%
“…Die anekdotische Evidenz deutet aber darauf hin, dass parteiübergeifende Abstimmungskoalitionen häufig sind. Je nachdem wie groß oder klein die Einflussmöglichkeiten des jeweiligen Parlaments bemessen sind, können Mitglieder der Regimelite und der Opposition an das Regime gebunden werden, während sie im Gegenzug verlässlichere Abmachungen mit der Führung treffen können Gandhi 2008, S. 80;Wright und Escriba-Folch 2012). Ein einheitliches Abstimmungsverhalten der meist aus den unteren Offiziersrängen rekrutierten und häufig wechselnden Militärs ist hingegen die Ausnahme (Egreteau 2015).…”
Section: Die Beziehungen Von Exekutive Und Legislativeunclassified
“…In unequal arenas of electoral competition, opposition parties thus have incentives to mobilize broad sectors of society in order to protest against the regime (see, e.g., Howard and Roessler 2006;Schedler 2013;Kinne and Marinov 2013). 4 Existing research has found a great deal of evidence consistent with this claim and shows that political parties constitute an important source of instability and conflicting interactions between regimes and opposition actors (Wright and Escribà-Folch 2012;Schedler 2013; Hafner-Burton, Hyde, and Jablonski 2014). Opposition parties often constitute the roots of political conflict and subversion since they can help actors overcome barriers to collective action (Aksoy, Carter, and Wight 2012).…”
Section: Authoritarian Legislatures Opposition Parties and Repressionmentioning
confidence: 99%